Energy Recovery from Cooling Tower Blowdown Water for Micro-Hydropower Generation: A Case Study at Asam Asam Coal-Fired Power Plant - Handa Ramadhan; Rachmawan Budiarto; Kusnanto Kusnanto (International Journal Labs, 2026)
The global electricity sector faces increasing pressure to maintain reliable supply while reducing greenhouse gas emissions. In coal-fired power plants, cooling tower blowdown water is typically discharged as wastewater, despite containing hydraulic energy potential. This study aims to evaluate the technical, environmental, and financial feasibility of utilizing cooling tower blowdown water for low-head micro-hydropower generation at the Asam Asam Coal-Fired Power Plant in South Kalimantan, Indonesia. The research methodology combines field measurements of flow and head, hydraulic and turbine design, annual energy modeling, carbon emission reduction estimation, and financial analysis including NPV, IRR, Payback Period, and LCOE. Results indicate that the selected cooling towers, with a Q?? discharge of 0.15 m³/s and gross head of 4 m, can generate 25,379–25,996 kWh/year, supplying approximately 85.42% of the mosque's annual energy demand. The system can reduce CO? emissions by 31.80–32.57 tons per year and demonstrates financial feasibility with an NPV of IDR 43,043,390.85 and a payback period of just over seven years. In conclusion, cooling tower blowdown water represents a viable energy recovery source, contributing to operational sustainability and emission reduction. The study recommends future exploration of hybrid energy systems and optimization for larger-scale industrial applications.